Application and Practice of Variable Axial Force Cable in Powerhouse Truss Reinforcement System - Zizhen Shen; Min Hong; Xunfeng Li; Zigang Shen; Lianbo Wang; Xueping Wang (Buildings, 2023)
Long-span steel structure trusses are widely used in factory buildings. However, with the increase in service time and dynamic load fatigue, transverse cracks at the bottom of the middle span and oblique deformation of the abdomen during the operation process may appear in a considerable part of long-span trusses with dynamic load. The U-shaped cracks at the bottom and belly, as well as the mid-span down deflection of the main truss, can also reduce the functionality of the factory building truss structure and limit the original crane load, thus affecting the normal safety and durability of the structure. Therefore, the principle of variable axial force cable system in the long-span factory building truss structure and 3D3S software modelling were applied. Analysing and studying the reinforcement method of large-span powerhouse trusses can provide practical experience for subsequent similar projects. In view of the above phenomenon, the large-span powerhouse trusses of Hongcheng Powerhouse No. 1 and No. 2, located in Tonglu, Zhejiang Province, were used as the research objects, and the variable axial force cable method was proposed to strengthen and lift the load. Considering the span of the powerhouse truss, a cable system with 22 m and a controlling force of 400 kN was proposed for Powerhouse 1, and a cable system with a variable axial force of 24 m was proposed for Powerhouse 2. The force model of large-span trusses was established by using the finite element method, which is commonly used to analyse the force of the truss. The influence of the reinforcement effect was analysed under two working conditions and compared from three aspects: stiffness, bearing capacity and stability. Furthermore, the phenomenon of uneven stress distribution was analysed. The stress distribution characteristics of each node were understood by simulating the most disadvantageous node plates with the greatest internal force before and after reinforcement.